2022
DOI: 10.3390/vaccines11010014
|View full text |Cite
|
Sign up to set email alerts
|

Association between COVID-19 Primary Vaccination and Severe Disease Caused by SARS-CoV-2 Delta Variant among Hospitalized Patients: A Belgian Retrospective Cohort Study

Abstract: We aimed to investigate vaccine effectiveness against progression to severe COVID-19 (acute respiratory distress syndrome (ARDS), intensive care unit (ICU) admission and/or death) and in-hospital death in a cohort of hospitalized COVID-19 patients. Mixed effects logistic regression analyses were performed to estimate the association between receiving a primary COVID-19 vaccination schedule and severe outcomes after adjusting for patient, hospital, and vaccination characteristics. Additionally, the effects of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…Understanding the influence of COVID-19 vaccinations on ARDS is critical. Fortunately, primary vaccination against SARS-CoV-2 infection prevents the development of ARDS and death in patients hospitalized after COVID-19 infection (Robalo et al, 2023). Similarly, in-hospital mortality could also been reduced in mechanically ventilated COVID-19 induced ARDS patients after the full vaccination (Siempos et al, 2022).…”
Section: Impact Of Covid-19 Vaccines In Acute Respiratory Distress Sy...mentioning
confidence: 99%
“…Understanding the influence of COVID-19 vaccinations on ARDS is critical. Fortunately, primary vaccination against SARS-CoV-2 infection prevents the development of ARDS and death in patients hospitalized after COVID-19 infection (Robalo et al, 2023). Similarly, in-hospital mortality could also been reduced in mechanically ventilated COVID-19 induced ARDS patients after the full vaccination (Siempos et al, 2022).…”
Section: Impact Of Covid-19 Vaccines In Acute Respiratory Distress Sy...mentioning
confidence: 99%
“…A large amount of evidence has indicated that vaccinations are particularly effective in reducing the incidence of severity and mortality among COVID-19 patients [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. To date, more than 200 COVID-19 vaccine candidates are in various stages of development, and more than 50 of these candidates have started clinical trials.…”
Section: Introductionmentioning
confidence: 99%